NordiQC Assessments of Chromogranin A Immunoassays. Issue 4 (April 2019) - Røge, Rasmus; Kristoffersen, Heidi L.; Bzorek, Michael; Nielsen, Ole; Vyberg, Mogens
Abstract : This paper is number 6 in a series developed through a partnership between ISIMM and Nordic IHC Quality Control with the purpose of reporting research assessing the performance characteristics of immunoassays in an external proficiency testing program.